EVALUASI CADANGAN MINYAK ZONA A DAN B, LAPANGAN RAMSES, BLOK D, MELALUI PEMODELAN GEOLOGI BERDASARKAN DATA PETROFISIKA - Iqbal, Prahara; Mardiana, Undang (Teknologi Indonesia, 2009)
Geology modelling has been done in Zone A and B, Ramses field, Blok D. The modelling was conducted by determining Zone A and B as zone having to be checked based on gamma ray, resistivity, and densitiy curve integrity reading (qualitative analysis) and petrophysic analysis which used GS software (quantitative analysis). Then the data were entered into IRAP RMS 7.3 software. The results are Zone A and B geology modelling and also oil concentration modeling which describe the biggest area of oil concentration, plus the oil amount. the result showed that, the biggest area of oil concentration is at south of each zone. The oil amount are: Zone A=82,78 million barrel, Zone B=36.08 million barrel.